A study on the impact of ethics marketing and sustainable marketing on sustainable purchasing behavior of consumers in Ho Chi Minh City - Hoang, Cuu Long; Phan, Thi Thu Hang; Lai, Doan Anh Tuan; Ho, Thi Hieu (Journal of Finance - Marketing Research, 2025)
This study examines how ethical and sustainable marketing strategies shape sustainable consumer behavior in Ho Chi Minh City. Focusing on the roles of ethics marketing, sustainable marketing, and social media marketing (SMM), the research explores how these approaches interact to influence sustainable purchase intentions and actual behavior. A survey of 1,512 urban consumers was conducted, and the structural model was tested using SEM. Results indicate that ethics marketing enhances sustainable marketing, which subsequently improves SMM performance. However, ethics marketing also exerts a small but significant negative effect on SMM, reflecting consumer skepticism toward ethical claims on digital platforms. While SMM strongly drives intention, the translation into actual purchasing behavior remains limited due to barriers such as price sensitivity and restricted product availability. The study contributes to the literature by clarifying the interconnected roles of ethical, sustainable, and digital marketing in shaping consumer responses. It also offers practical guidance for marketers and policymakers to develop credible sustainability communication and address the persistent intention-behavior gap.